Systemic model of segregation and transformation of urban solid waste - Alex Rengifo Rojas; Nelino Florida Rofner; Luis Morales y Chocano; José Raúl Rodríguez Lichtenheldt; Julio Pedro Atoche Cornejo (Cleaner Engineering and Technology)
In developing countries, the solid waste generated is rarely segregated, unused, and often lacks proper final disposal due to a lack of infrastructure, equipment, and personnel in municipalities. This study analyzes the composition of the waste generated in the city of Tingo María through modeling and simulation with system dynamics, seeking to optimize its transformation, recycling and final disposal. Simple and cluster random sampling methods were used to select 119 households and 229 non-domestic establishments, in addition to non-random sampling for 26 special establishments. The waste was classified and weighed into categories of organic, useable inorganic and non-useable, differentiating between domestic, non-domestic and special waste. In the modeling stage with system dynamics, @Risk 7.5 for Excel and Stella 9.0.2 were used, incorporating population and waste volume data. These values were adjusted to a probability distribution function and expressed in state, flow and auxiliary equations, to explain and predict their behavior. The results of the model indicate that the amount of population and its consumption culture are determining factors in calculating the generation of waste of each type. Organic waste has a greater growth trend than inorganic waste, which allows us to project the viability of producing compost, foliar fertilizer and biogas. Likewise, useable inorganics, also on the rise, could generate income through their sales, thus reducing the amount of waste destined for landfill. The modeling suggests the construction of new infrastructures for the transformation of organic solid waste and the development of sanitary landfills. In addition, for effective management of the system, it is essential to raise awareness and train the population in practices of segregation at source, recycling and reuse, thus optimizing the economic and environmental benefits of an adequate final disposal of the waste generated.